Developing Rural Markets for Solar Products: Lessons from Ghana - William, F.S; Anyidoho, N.A; Dadzie, F.Y; Hosier, R.H (Elsevier Inc., 2016)
This paper assesses market development as a sustainable approach to increasing the use of renewable energy, specifically solar, using the case of Ghana's Solar Project. This strategy is intended to overcome some weaknesses of donor-driven and fee-for-service models in sustaining gains beyond the end of projects. The literature shows that developing a sustainable market for solar products in under-served rural areas requires an integrated approach addressing demand, supply, financing, quality, and facilitation. The Ghana Solar Project was well designed to overcome constraints in all of these areas. Results were positive in terms of numbers of systems purchased and impact on perceived benefits and willingness to pay. Benefits were documented with respect to education, information, mobile phone charging, income generation, and health and fire risks. Competition increased, and system costs fell. Financial institutions expanded their products and outreach, and inmost cases had good recovery rates. Nevertheless, sustained market growth may be constrained by the lack of local technicians and spare parts and by possible withdrawal of some local Rural and Community Banks from providing financing and Solar Project Officers to facilitate the process, in the absence of a line of credit and results-based bonuses.
Keywords: Developing; Rural Markets